MENUJU KEMANDIRIAN DAN PARTISIPASI DALAM ORGANISASI HIPPA / GHIPPA MASYARAKAT DESA MRANGGONLAWANG KABUPATEN PROBOLINGGO - Ariyanti, Dyah; Mustakim, Mustakim; Haryono, Haryono; K, Dwi Putri; Iswardani, Kurnia (Abdi Panca Marga, 2024)
ABSTRACT The phenomenon of warming sea surface temperature, or what is often called El Nino, has the impact of reducing rainfall in Indonesia, causing a very long dry season in 2023 - 2024. BMKG stated that a number of regions in Indonesia have monthly rainfall intensity in the low category, so the dry season is drier than the previous 3 (three) years. The impact of El Nino has become a natural phenomenon that has an influence on the people of Java Island, especially the Probolinggo Regency area. Most of the people of Probolinggo Regency use their land as agricultural land. Mranggonlawang Village is an area that has the potential to be successful with its agricultural products, especially shallots. Where 40.77% of the agricultural land in the village is dry land, 27% is paddy land and 32.13% is homestead. The problems that occur in Mranggonlawang village are due to human resources (HR) constraints which have not been maximized in managing existing natural resources, so they only depend on shallot farming. The community is not aware that natural resource management regarding irrigation of agricultural land can be utilized, because water sources in Mranggon Lawang village are abundant. Therefore, it is necessary to form an association so that water in Mranggonlawang village can be managed as well as possible. This water association is part of the Association of Water User Farmers (HIPPA) or the Association of Water User Farmers Associations (GHIPPA). Keywords: El Nino, Mranggonlawang, HIPPA, GHIPPA